1999
DOI: 10.1164/ajrccm.159.1.9712041
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Hematopoietic Chimerism Induces Donor-specific Tolerance for Lung Allografts in Rodents

Abstract: Mixed hematopoietic chimerism is a state in which bone marrow hematopoietic stem cells from two genetically different animals coexist. We investigated whether mixed hematopoietic chimerism, resulting from the transplantation of host and donor bone marrow into a lethally irradiated rat, would confer donor-specific tolerance to lung allografts. Recipient rats (Fisher or or Wistar Furth [WF]) were irradiated (1,100 cGy) and reconstituted with a mixture of T-cell-depleted syngeneic plus allogeneic bone marrow. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
(33 reference statements)
0
24
0
Order By: Relevance
“…They have also reported that mixed hematopoietic chimerism induces donor-specific tolerance for lung allografts in rats. 5 In their study, they prepared mixed chimeric rats, in which T cell-depleted syngeneic plus donor BMCs were transplanted into irradiated recipients; 4 weeks later, lung transplantation was carried out. However, it would be difficult to apply this method to clinical lung transplantation from cadavers.…”
mentioning
confidence: 99%
“…They have also reported that mixed hematopoietic chimerism induces donor-specific tolerance for lung allografts in rats. 5 In their study, they prepared mixed chimeric rats, in which T cell-depleted syngeneic plus donor BMCs were transplanted into irradiated recipients; 4 weeks later, lung transplantation was carried out. However, it would be difficult to apply this method to clinical lung transplantation from cadavers.…”
mentioning
confidence: 99%
“…In addition, we have recently shown the same findings in the transplantation of combinations of BMCs and other organs or tissue (such as the skin, leg and lung 18,[37][38][39] as in PI transplantation. Pham et al 40 and Foster et al 41 have also shown the importance of the existence of donor hematopoietic cells for the acceptance of the lung and composite tissue in the transplantation of the combination of BMCs and organs. The absence of a response of T cells in the PI-accepting rats to both recipient and donor MHC determinants in MLR suggests the induction of tolerance in the PI-accepting rats, resulting in long-term acceptance of the grafted PIs without the use of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Lethally irradiated rats reconstituted with chimeric T-cell-depleted syngeneic and allogeneic bone marrow accepted orthotopic lung and heterotopic tracheal transplants indefinitely, with minimal histopathologic evidence of rejection. 46,47 In 1 clinical series, increased peripheral-blood allogeneic microchimerism correlated with freedom from OB. 48…”
Section: Tolerancementioning
confidence: 97%